Correlation of cyclin D1, HER2, and AMACR expressions with histologic grade in bladder urothelial carcinomas - Yeliz Arman Karakaya; Esin Oral (Wolters Kluwer Medknow Publications, 2021)
Background and Objective: Bladder cancer is the ninth most common type of cancer worldwide. We aimed to investigate the relationship between tumor grade, lamina propria invasion, muscularis propria invasion, and lymphovascular invasion and human epidermal growth factor receptor 2 (HER-2), cyclin D1, and alpha-methyl-CoA racemase (AMACR) expressions in bladder cancer. Materials and Methods: The study included patients who underwent complete TURBT. In total, 72 cases of bladder cancer diagnosed by two pathologists were selected. AMACR, HER-2, cyclin D1 expressions were detected immunohistochemically. Results: The study population comprised 80% (57) males and 20% (15) females (mean age, 68 years). Further, 35 cases were noninvasive and 37 invasive urothelial carcinoma and 38 patients had low-grade tumor and 34 high-grade tumor. Intense immunostaining was observed with cyclin D1 for 75% tumors, AMACR for 39%, and HER-2 for 86%. High expressions of cyclin D1 and AMACR were observed in high-grade tumors (P < 0.05 and P < 0.005, respectively). High expression of HER-2 (2 and 3 positive) was found both at low- and high-grade tumors (84% and 88%, respectively). Conclusion: Cyclin D1, AMACR expressions were found to be significant predictive factors of high-grade tumors. High Her-2 expression in patients with bladder carcinoma may indicate that they are potential targets for treatment. These markers may be important in determining prognosis of tumors and may be valuable for guiding treatment options.